Negotiating labor-management contracts - Cullen, Donald E. (Ithaca, N.Y., New York State School of Industrial and Labor Relations, Cornell University, 1965)
This bulletin explore several questions implicit in the above discussion of the collective bargaining in the conventional mode of negotiation in cognition with the labor contracts.
Bibliographical footnotes.
asm; 13/02/19
Loans
Keywords: Collective bargaining